Essays on European economic integration, institutions and fiscal rules - Lehtimäki, Jonne (fi=Turun yliopisto. Turun kauppakorkeakoulu|en=University of Turku, Turku School of Economics|, 2026)
This doctoral dissertation studies the economic effects of European integration and fiscal governance, focusing on the European Single Market and fiscal rules. The dissertation is comprised of an introductory chapter and four independent essays. It applies a combination of the Synthetic Control Method (SCM) and panel data analysis to evaluate effects on economic growth and public finances. The first essay uses the SCM to empirically evaluate the economic growth effects of the European Single Market. The results show that the single market has generated significant real GDP per capita increases with smaller member states benefiting more substantially than larger countries. The study highlights the role of trade liberalisation in enhancing economic performance. The second essay, also using the SCM, studies the impact of European integration and European Union's (EU) fiscal framework on government debt levels. The results show that both EU membership and the establishment of the Stability and Growth Pact (SGP) have had significant debt-limiting effects across a large majority of the studied country groups and individual member states. The results imply that actual government debt levels in EU countries are considerably lower than they would have been without common fiscal rules, even for countries with low compliance. The third essay builds upon the second and compares the effects of national and supranational fiscal rules on government debt across EU member states. The results indicate that the SGP has effectively reduced government debt. National fiscal rules show varying levels of effectiveness. The findings indicate that fiscal rules often complement rather than substitute each other and it is important to account for the interaction between national and EU-level fiscal frameworks. The final essay extends the analysis beyond Europe and examines the effects of national and supranational fiscal rules in a global sample. It analyses their impact on government debt, government budget balances, public investment and economic growth. The results suggest that supranational rules outperform national ones in ensuring fiscal discipline, while also confirming the complementarity of different rules. Although fiscal rules generally target fiscal variables, the study also identifies some potential spillover effects on economic growth.

---- Tämä väitöskirja käsittelee Euroopan taloudellista integraatiota ja finanssipoliittisia kehikoita, keskittyen Euroopan sisämarkkinoihin ja finanssipoliittisiin sääntöihin. Työ koostuu johdannosta ja neljästä itsenäisestä esseestä. Tutkimuksessa sovelletaan synteettistä kontrollimetodia (SCM) ja paneeliaineistoja talouskasvun sekä julkisen talouden vaikutusten tutkimiseen. Ensimmäisessä esseessä arvioidaan Euroopan sisämarkkinoiden talouskasvuvaikutuksia empiirisesti SCM:n avulla. Tulokset osoittavat, että sisämarkkinat ovat tuottaneet merkittävää kasvua tarkasteltaessa reaalista BKT:ta asukasta kohden ja pienikokoisemmat jäsenvaltiot ovat hyötyneet kaupankäynnin esteiden poistumisesta huomattavasti suurempia maita enemmän. Toisessa esseessä tutkitaan SCM:n avulla Euroopan unionin (EU) ja sen finanssipoliittisen kehikon vaikutusta jäsenvaltioiden julkisen velan tasoihin. Tulokset osoittavat, että EU-jäsenyydellä sekä vakaus- ja kasvusopimuksella on ollut merkittäviä julkista velkaa rajoittavia vaikutuksia valtaosassa tutkittuja maaryhmiä ja yksittäisiä jäsenvaltioita. Tulosten mukaan EU-jäsenvaltioiden toteutuneet velkatasot ovat huomattavasti alhaisempia kuin ne olisivat olleet ilman yhteisiä finanssipoliittisia sääntöjä. Kolmas essee vertailee kansallisten ja ylikansallisten finanssipoliittisten sääntöjen vaikutuksia julkiseen velkaan EU:n jäsenvaltioissa. Tulokset osoittavat, että vakaus- ja kasvusopimus on laskenut julkisen velan tasoja. Kansallisten finanssipoliittisten sääntöjen tehokkuus on vaihtelevaa. Tulokset osoittavat lisäksi, että finanssipoliittiset säännöt toimivat usein komplementteina, ja siksi on tärkeää huomioida finanssipoliittisten kehikoiden välinen vuorovaikutus. Viimeinen essee tutkii kansallisten ja ylikansallisten finanssipoliittisten sääntöjen vaikutuksia maailmanlaajuisessa otoksessa. Se analysoi sääntöjen vaikutusta julkiseen velkaan, julkisen talouden nettorahoitusasemaan, julkisiin investointeihin ja reaaliseen talouskasvuun. Tulosten mukaan ylikansalliset säännöt toimivat kansallisia paremmin julkisen talouden hallinnassa, vahvistaen samalla eri sääntöjen komplementaariset vaikutukset. Finanssipoliittiset säännöt keskittyvät yleensä pääasiassa julkisen talouden muuttujiin, mutta tulosten perusteella niillä on epäsuoria vaikutuksia myös talouskasvuun.